Intervention Strategies For The Microbiological Safety Of Foods Of Animal Origin - Doyle, Michael P.; Acuff, Gary R.; Cords, Bruce; Cullor, James; Hollingsworth, Jill; Penner, Karen P.; II, Robert A. Seward; Sperber, William H.; Tompkin, Bruce (Council for Agricultural Science and Technology (CAST), 2004)
Prepared by a task force of thirteen scientists, this issue paper provides a timely consideration of critical issues:microbiological safety of foods of animal origin during production; food processing strategies for manufactured foods of animal origin, both ready-to-cook and ready-to-eat; food safety initiatives in retailing; consumer interventions to enhance food safety; challenges to applying food safety controls uniformly across all sectors of the food service industry; and recommendations for development and application of new intervention strategies to decrease human illnesses attributed to foods derived from animals.